IZOENZYME STRUCTURE OF POPULATIONS OF TICKS IXODES PERSULCATUS SCHULZE (ACARI: IXODIDAE) IN RECREATION AREAS OF IRKUTSK CITY - Yu. P. Dzhioyev (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Allozyme structure of the population of ticks Ixodes persulcatus in 8 enzyme systems is shown in two samples of ticks from the recreational areas in suburbs of Irkutsk. From the total of 13 loci, which encode these enzymes, eight were polymorphic. Based on allozyme analysis of populations of mites, it is found that most of them show intrapopulation heterogeneity and. the lack of difference between the two populations from different foci. A similar pattern may indicate a large rate of migration of genes between populations and. their close relatives.